2013
DOI: 10.1200/jco.2013.31.15_suppl.3508
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, placebo-controlled, phase I/II study of tivantinib (ARQ 197) in combination with cetuximab and irinotecan in patients (pts) with KRAS wild-type (WT) metastatic colorectal cancer (CRC) who had received previous front-line systemic therapy.

Abstract: 3508 Background: Tivantinib (ARQ 197) selectively inhibits the MET receptor tyrosine kinase, which is implicated in tumor cell migration, invasion, and metastasis. Resistance to EGFR inhibitors has been associated with activation of alternative pathways including MET. Methods: Pts with advanced KRAS WT CRC that progressed on or after 1 prior line of chemotherapy and no previous treatment with an EGFR inhibitor were eligible. Pts were randomized 1:1 to receive cetuximab (500 mg/m2) and irinotecan (180 mg/m2) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Although this finding could be due to chance, it is in line with an exploratory analysis of the monoclonal antibody ficlatuzumab in NSCLC, which demonstrated that the addition of ficlatuzumab to gefitinib appeared to benefit patients with low tumoral MET expression . In addition, a subgroup analysis of a phase Ib study in colorectal cancer showed that patients with low MET expression tumors derived a statistically significant improvement in PFS with the possible anti‐MET TK inhibitor tivantinib . These results indicate a complex and as yet not understood relationship between MET expression and tumor response to anti‐MET agents.…”
Section: Discussionsupporting
confidence: 65%
“…Although this finding could be due to chance, it is in line with an exploratory analysis of the monoclonal antibody ficlatuzumab in NSCLC, which demonstrated that the addition of ficlatuzumab to gefitinib appeared to benefit patients with low tumoral MET expression . In addition, a subgroup analysis of a phase Ib study in colorectal cancer showed that patients with low MET expression tumors derived a statistically significant improvement in PFS with the possible anti‐MET TK inhibitor tivantinib . These results indicate a complex and as yet not understood relationship between MET expression and tumor response to anti‐MET agents.…”
Section: Discussionsupporting
confidence: 65%
“…After describing Bcl-xl, Mcl-1 and Cyclin B1 as functional targets of tivantinib in determining apoptosis and cell cycle arrest, we assessed whether the influence of tivantinib on these molecules is dependent on its efficacy as inhibitor of c-MET, as the predictive significance of this receptor in clinical trials seems to suggest [ 2 , 16 ]. To this aim, we assessed the effects of c-MET silencing by siRNA transfection in Huh7 cells; additionally, we compared the effect of tivantinib on DLD1 cells, which express the native form of c-MET vs. that on syngenic DLD1 c-MET exon 16 KO cell lines, which express a genetically modified variant of c-MET lacking the binding site of tivantinib.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of promising signals of activity of the anti-MET TKI tivantinib in a Phase IB study in colorectal cancer where four of nine patients had an objective response, a combination study of irinotecan–cetuximab (Erbitux, Merk-Serono) with or without this drug was investigated in a randomized, Phase II trial in a population of KRAS wild-type metastatic colorectal cancer patients (n=122) who had progressed on or after one line of systemic therapy. 76 , 77 Tivantinib in combination with standard treatment was associated with a higher response rate (45% versus 33.3%) and a slight improvement in PFS (8.3 versus 7.3 months, respectively); however this was not statistically significant (PFS HR 0.85, P =0.38). Surprisingly, but in line with what has been observed with ficlatuzumab in NSCLC, a subgroup analysis conducted in a small number of study patients showed a statistically significant improvement in PFS with tivantinib in patients with low-MET-expressing tumors; however this subgroup contained only 23 patients and requires validation in a larger patient cohort.…”
Section: Met In Colorectal Cancermentioning
confidence: 93%